LARA as a language-independent aspect-oriented programming approach - Pinto, P (2017)
Usually, Aspect-Oriented Programming (AOP) languages are an extension of a specific target language (e.g., AspectJ for Java and AspectC++ for C++). This coupling can impose drawbacks such as arbitrary limitations to the aspect language. LARA is a DSL for source-to-source transformations inspired by AOP concepts, and has been designed to be independent of the target language. In this paper we propose techniques to overcome some of the challenges presented by a language-independent approach to source code transformations, and present and discuss possible solutions and their impact. Additionally, we present some of the benefits and opportunities of this approach. We present an evaluation of our approach, show that we can significantly reduce the effort to develop weavers for new target languages and that the proposed techniques contribute to more concise LARA aspects and safer semantics. Copyright 2017 ACM.